2013
DOI: 10.1002/stem.1301
|View full text |Cite
|
Sign up to set email alerts
|

Individual Hematopoietic Stem Cells in Human Bone Marrow of Patients with Aplastic Anemia or Myelodysplastic Syndrome Stably Give Rise to Limited Cell Lineages

Abstract: Mutation of the phosphatidylinositol N-acetylglucosaminyltransferase subunit A (PIG-A) gene in hematopoietic stem cells (HSCs) results in the loss of glycosylphosphatidylinositol-anchored proteins (GPI-APs) on HSCs, but minimally affects their development, and thus can be used as a clonal maker of HSCs. We analyzed GPI-APs expression on six major lineage cells in a total of 574 patients with bone marrow (BM) failure in which microenvironment itself is thought to be unaffected, including aplastic anemia (AA) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…GPI-AP À cells are far more frequent in the myeloid than in the lmphoid compartment. (Katagiri et al, 2013). Proportions of GPI-AP À cells were significantly higher in granulocytes than in HSCs ( Figure S5), and our data suggested that higher CXCR2 expression might explain the dominance of GPI-AP À cells in myeloid cells in PNH.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…GPI-AP À cells are far more frequent in the myeloid than in the lmphoid compartment. (Katagiri et al, 2013). Proportions of GPI-AP À cells were significantly higher in granulocytes than in HSCs ( Figure S5), and our data suggested that higher CXCR2 expression might explain the dominance of GPI-AP À cells in myeloid cells in PNH.…”
Section: Resultsmentioning
confidence: 59%
“…As CXCR2 ligands affect NF-κB activation in various cancer cells and promote cell survival, elevated CXCR2 level in GPI-AP − granulocytes might also represent a growth advantage. GPI-AP − cell prevalence is high in myeloid cells and low in lymphoid cells (Katagiri, et al 2013). Proportions of GPI-AP − cells were significantly higher in granulocytes than in HSCs (Fig S5), and our data suggested that higher CXCR2 expression might explain the dominance of GPI-AP − cells in myeloid cells in PNH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, duration of prior IST from sampling date was quite long, and immunosuppressive therapies were not being administered to any patient at the time of sampling. GPI-AP - T cells were not examined, due to the low frequency of this population (78). As our T cells were unstimulated, it is possible that we failed to detect difference in gene expression apparent only on activation.…”
Section: Discussionmentioning
confidence: 99%
“…16 The proportion of FLAER 2 PNH cells in each cell population varied among the first samples taken from all 6 patients, consistent with previous reports. [17][18][19] Granulocytes and monocytes had the highest proportions of FLAER 2 cells in all 6 patients (ranges, 68.5% to 100% and 75.3% to 100%, respectively; Figure 1C; supplemental Table 3). The absolute number of B1 cells varied among the samples and ranged from 2.17 3 10 6 /L to 14.52 3 10 6 /L ( Figure 1D; supplemental Table 4).…”
Section: Pnh01 C a T T C C C T T A T T T G T G T G A C A G G T A T T mentioning
confidence: 99%